2018
DOI: 10.1515/humo-2017-0033
|View full text |Cite
|
Sign up to set email alerts
|

Influence of neural mobilization of lower limbs on the functional performance and dynamic balance in asymptomatic individuals: a cross-over randomized controlled trial

Abstract: Purpose. To verify the influence of neural mobilization (NM) applied to the lower limbs on functional performance and dynamic balance in asymptomatic individuals. Methods. The total of 30 asymptomatic participants (15 women and 15 men; age, 30.1 ± 6.7 years; height, 1.70 ± 0.1 m; body mass, 73.1 ± 13.4 kg) were enrolled in this cross-over randomized controlled trial. The participants received NM of the femoral, sciatic, and tibial nerves, as well as static stretching (SS) of the following muscles: hamstring, l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 29 publications
1
3
0
Order By: Relevance
“…7 Nunes et al compared the effects of nerve slider and tensioner technique applied to femoral, sciatic and tibial nerves to static stretch on vertical jump and dynamic balance assessed using star excursion balance test and reported no difference between interventions for any of the measures. [12][13][14][15][16][17][18] Findings are similar in present study, in both the groups improvement in Y-balance test is seen but it is more significant in anterior (p=0.00, 0.04) and right side (p=0.004, 0.003) in comparison to left side (p=0.012.0.041) of Y-balance test (Table 2).…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…7 Nunes et al compared the effects of nerve slider and tensioner technique applied to femoral, sciatic and tibial nerves to static stretch on vertical jump and dynamic balance assessed using star excursion balance test and reported no difference between interventions for any of the measures. [12][13][14][15][16][17][18] Findings are similar in present study, in both the groups improvement in Y-balance test is seen but it is more significant in anterior (p=0.00, 0.04) and right side (p=0.004, 0.003) in comparison to left side (p=0.012.0.041) of Y-balance test (Table 2).…”
Section: Discussionsupporting
confidence: 82%
“…8,10,11 Neurodynamic technique or neural mobilization is multidimensional manual technique which helps to improve neural and non-neural tissue function. 12,13 It release tension in the nerve 14,15 by moving one or several joints to stretch the nerve bed through both the ends and decreases the neural mechanosensitivity and thus helps in increasing hamstring flexibility and helps to restore dynamic balance. 11,16 Neurodynamic Slider (NS) is a type of neural mobilization where one end of the neural tissue is elongated and another end is 17 Neurodynamic Tensioner (NT) is another type of neural mobilization where joint movements are performed simultaneously in which the tension is applied on both sides of the neural structures in order to lengthen the nerve bed.…”
Section: Introductionmentioning
confidence: 99%
“…Examination of the literature revealed that some studies used the threshold of vibration perception or thermal perception as a criterion for the sense of pain (Beneciuk et al, 2009;Kumar et al 2010); however, some studies have assessed the pain threshold with an algometer-as was the case in the present study (Lalouni et al, 2021;de Dios Perez-Bruzon et al, 2022). Studies that selected subjects with similar pathologies have found that the pain decreased with the application of neural mobilization (Pedersini et al, 2021;Peacock et al, 2022); whereas in studies with healthy cases, the results of neural mobilization on pain varied from effective to ineffective (Beneciuk et al, 2009;Nunes et al, 2017;Sousa Filho et al, 2017). Kumar et al suggested that the efficacy mechanism of neural mobilization on pain might be caused by firing afferent kinesthetic impulses with motion components during neural mobilization.…”
Section: Discussionmentioning
confidence: 99%
“…For example, there are reports that both techniques have positive and equivalent impact on hamstring flexibility 23 , hop testing and static postural control 14 , that gliding has superior hypoalgesic effects than tensioning 15 or that none of the techniques has a positive impact on postural control 24 . In addition to the reduced number of existing studies comparing gliding and tensioning, studied effects are limited to immediate post-intervention effects on the ipsilateral side of mobilization.…”
Section: Accepted Manuscriptmentioning
confidence: 99%